The impact of the introduction of formalised polypectomy assessment on training in the UK. Issue 2 (21st July 2016) - Patel, Kinesh; Faiz, Omar; Rutter, Matt; Dunckley, Paul; Thomas-Gibson, Siwan
Abstract : Objective: The aim was to describe the impact on polypectomy experience by the mandatory introduction of the Directly Observed Polypectomy Skills tool (DOPyS) and electronic portfolio as part of the formal colonoscopy certification process. Design: Applications for colonoscopy certification in the UK in the year prior to the introduction of DOPyS were analysed retrospectively and compared with data collected prospectively for those in the following year. Setting: UK National Health Service. Patients: None. Interventions: None. Main outcome measures: The outcomes studied included whether evidence of exposure to polypectomy, endoscopic mucosal resection (EMR) and colonoscopy changed over the 2-year period. The nature of the polyps removed by trainees was also studied. Results: Thirty two per cent of candidates in the first year had evidence of any observed polypectomy with 7% of candidates referring to training in EMR. The median number of formative colonoscopy assessments was 3 (range 0–16). All of these candidates in the second year had evidence of polypectomy assessment, with a median number of DOPyS of 7 (range 3–27). Eighty nine per cent of applicants had evidence of assessed EMR. The median number of formative colonoscopy assessments in this cohort was 32 (range 9–199). There was a significant increase in the number of logged polypectomy assessments (p<0.001), experience of EMR (p<0.001) and formative colonoscopy assessments (p<0.001). There was no significant difference in the total number of colonoscopy procedures performed. Conclusions: Structured polypectomy assessment improves trainees' documented exposure to therapeutic endoscopy as well as providing formal evidence of skills acquisition. As polypectomy plays an increasing role globally in colorectal cancer prevention, the DOPyS provides an effective means of assessing and certifying polypectomy.